Herbal combination therapy of coriander and red ginger extracts to improve hematological profiles in hyperlipidemia: in vivo study - Puspitasari, Puspitasari; Aliviameita , Andika; Puspita , Anggun; Ibnu Mubaroq Ramadhan , Syahrul (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2025)
Background: Herbal therapies offer promising alternatives for managing hyperlipidemia-induced hematological disorders. This study focuses on the combined effects of Coriandrum sativum L. (coriander) and Zingiber officinale var. rubrum (red ginger) extracts on hematological profiles in hyperlipidemic conditions. While prior studies mainly investigated these extracts individually, their combined therapeutic potential remains underexplored. Objective: To evaluate the effects of coriander and red ginger extracts, individually and in combination, on erythrocyte count, hemoglobin level, and hematocrit in rats with induced hyperlipidemia. Methods: An experimental pre-test–post-test control group design was conducted on male Rattus norvegicus. Hyperlipidemia was induced by a high-fat diet and 0.01% PTU for 15 days. Rats were divided into four groups: hyperlipidemia control, red ginger extract (875 mg/kgBW), coriander extract (900 mg/kgBW), and a 1:1 combination. Hematological parameters were measured on days 16 and 32. Data were analyzed using two-way ANOVA. Results: Coriander and red ginger extracts significantly improved erythrocyte count, hemoglobin concentration, and hematocrit levels in hyperlipidemic rats (p = 0.000). Conclusions: Combined administration of coriander and red ginger extracts effectively enhances hematological profiles in hyperlipidemia, supporting their potential as an alternative herbal therapy.